Student drinking in the transition to university and across the first academic year - Fuller, Amy (2019)
Previous research has shown that high numbers of students drink hazardously or harmfully, or binge drink, but little is known about how drinking patterns establish or develop for this population. The purpose of this thesis was to understand this further by exploring patterns of, experiences with and potential influences upon drinking among young adults as they transition to university and across their first academic year. A sequential, with embedded concurrent, mixed-methods design was adopted, consisting of four studies which explored: 1) the nature of events and alcohol-related content students are exposed to at a university freshers’ fair; 2) students’ drinking patterns prior to university and across the first academic year; 3) the perceptions and experiences of both drinkers and abstainers, with alcohol, across the same time period; and 4) the views of staff who have a role in student experience and welfare on the university drinking culture.Many students came to university having engaged in or with an established pattern of binge drinking, but higher proportions reported doing so in the first month of university, more frequently and with higher quantities of alcohol. This remained elevated across the year. The increase appears to be initially driven by students’ expectations that drinking is central to socialising at university as well as an emphasis on alcohol-centred events from the Students’ Union during freshers’ week. Student-led groups emerged as a potentially important influence upon student drinking as they had a strong influence over the nature of social events from freshers’ week and beyond, with many of the events that they advertised in their freshers’ fair materials and organised throughout the year centred on drinking heavily. Many drinkers and abstainers, however, wanted a more socially inclusive environment where drinking was not the focus. Staff provided examples of where they had attempted to address the binge drinking culture, to reduce adverse incidents resulting from heavy drinking and make the university more inclusive to light- and non-drinkers, although efforts were fragmented highlighting the need for policy to ensure a consistent and comprehensive approach on student drinking.